Clinicians and patients perspectives on follow-up care and eHealth support after allogeneic hematopoietic stem cell transplantation: A mixed-methods contextual analysis as part of the SMILe study. (April 2020) - Leppla, Lynn; Mielke, Juliane; Kunze, Maria; Mauthner, Oliver; Teynor, Alexandra; Valenta, Sabine; Vanhoof, Jasper; Dobbels, Fabienne; Berben, Lut; Zeiser, Robert; Engelhardt, Monika; De Geest, Sabina; et al.
Abstract: Purpose: We report on our contextual analysis's methodology, as a first step of an implementation science project aiming to develop, implement, and test the effectiveness of an integrated model of care in SteM-cell transplantatIon faciLitated by eHealth (SMILe). Methods: We applied an explanatory sequential mixed-methods design including clinicians and patients of the University Hospital Freiburg, Germany. Data were collected from 3/2017 to 1/2018 via surveys in 5 clinicians and 60 adult allogeneic stem-cell transplantation patients. Subsequently, we conducted 3 clinician focus groups and 10 patient interviews. Data analysis followed a 3-step process: (1) creating narrative descriptions, tables, and maps; (2) mapping key observational findings per dimension of the eHealth-enhanced Chronic-Care Model; (3) reflecting on how findings affect our choice of implementation strategies. Results: Current clinical practice is mostly acute care driven, with no interdisciplinarity and weak chronic illness management. Gaps were apparent in the dimensions of self-management support and delivery-system design. Health behaviors that would profit from support include medication adherence, physical activity and infection prevention. The theme "being alone and becoming an expert" underpinned patients need to increase support in hospital-to-home transitions. Patients reported insecurity about recognizing, judging and acting upon symptoms. The theme "eHealth as connection not replacement" underscores the importance of eHealth augmenting, not supplanting human contact. Synthesis of our key observational findings informed eight implementation strategies. Conclusion: Stakeholders are willing towards a chronic care-focused approach and open for eHealth support. The contextual information provides a basis for the SMILe model's development and implementation. Highlights: eHealth-powered integrated models of care can potentially improve outcomes in alloSCT patients. Successful implementation of new care models require a thorough understanding of the context and needs. This report shows how context drives development and choice of implementation strategies to re-engineer alloSCT care. eHealth needs to be embedded within an integrated care model, supporting self-management and health behaviors. eHealth-powered care models can support continuity of care but should not replace human contacts.